PEMODELAN ALIRAN DAN REAKS DEHIDROGENASI ETHYLBENZENE MENJADI STYRENE DI REAKTOR MEMBRAN PORI TERMODIFIKASI - Purwandari, Siti
The models of reacting fluid in a membrane reactor has already been developed using simple two-dimensional mathematical approach. Two dimensional model could be used to understand the transport phenomena occur in a membrane reactor. The system is packed bed with Vycor glass membrane placed in the bed. Two system, N2 stream flows in to the tube and CgH10 into shell, are introduced into the system In this model, the convective and diffusion terms have a significant effect to transport process. Ethylbenzene dehydrogenation in a modified porous membrane reactor is used as a reaction model. The reactor consists of inner pipe and outer wall. It is made from a Vycor-glass membrane in which the separation of product reaction occurs and the outer wall is an impermeable wall. The dehydrogenation reaction occurs at 600-650Â°C and 2.4 bar on iron oxide catalyst dopped by potassium carbonate and chromium oxide which is placed in both annulus and inner cells. The reaction rate is controlled by several factor : the chemical reaction rate, pore diffusion and extrapellet diffusion. The computer programming for two dimensional mathematical model has been solved with compaq visual fortran 6.5. Momentum balance, continuity equation and mass balance has been discretized. By finishing the code the understanding of details transport phenomena in a real modified porous membrane reactor can be explained. The results of computer programming is distribution of velocity, pressure and component mass fraction